2017
DOI: 10.1186/s12889-017-4699-4
|View full text |Cite
|
Sign up to set email alerts
|

Is economic environment associated with the physical activity levels and obesity in Chinese adults? A cross-sectional study of 30 regions in China

Abstract: BackgroundBased on the 2014 survey of physical activity and physical fitness data of 20 − 69 year old Chinese, this study aims to investigate the relationship between economic development and people’s physical activity in China.MethodsA total of 43,389 adults from 30 different regions in mainland China were recruited. The GDP per capita of the 30 regions were determined based on the 2013 annual statistical report released by the national bureau of statistics of China and provincial level statistics bureaus. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…There is a relationship between the socioeconomic status of a country and levels of physical activity [ 15 ] and sedentary behavior [ 16 ]. For example, Wang et al found that people tended to engage in more physical activity in economically advanced regions in China, and the correlation coefficient between physical activity and gross domestic product (GDP) per capita was 0.23 for men and 0.15 for women [ 15 ].A systematic review and meta-analysis including 39 countries found that the prevalence of physical inactivity differed according to country GDP per capita. For example, the prevalence increased with GDP per capita in LMICs, but decreased in high-income countries [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a relationship between the socioeconomic status of a country and levels of physical activity [ 15 ] and sedentary behavior [ 16 ]. For example, Wang et al found that people tended to engage in more physical activity in economically advanced regions in China, and the correlation coefficient between physical activity and gross domestic product (GDP) per capita was 0.23 for men and 0.15 for women [ 15 ].A systematic review and meta-analysis including 39 countries found that the prevalence of physical inactivity differed according to country GDP per capita. For example, the prevalence increased with GDP per capita in LMICs, but decreased in high-income countries [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found no associations between demographic, macroeconomic, and human development determinants and sitting time. Previous studies investigated the association of demographic, macroeconomic, and human development determinants on physical activity and sitting time [14][15][16][17][18]. However, these studies investigated country-level macroeconomic, demographic, and human development determinants, with the inherent limitations that countrywide averages carry.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we need to consider country- and regional-level macroeconomic and demographic indicators among the South American countries. Previous studies, mainly focusing on developed countries, have found that higher macroeconomic, human development, and population density factors were associated with greater physical activity levels [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 Over half of the Chinese population is overweight or obese, and in mega-cities such as Beijing, overweight and obesity have always been serious problems. 7 , 8 With the rapid economic development of China, great changes have taken place in the lifestyle and physical activity habits of the inhabitants. 8 Among these changes, multiple factors such as lack of physical activity, unhealthy lifestyles, working stress, and environmental pollution may contribute to increased obesity and NCDs.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 With the rapid economic development of China, great changes have taken place in the lifestyle and physical activity habits of the inhabitants. 8 Among these changes, multiple factors such as lack of physical activity, unhealthy lifestyles, working stress, and environmental pollution may contribute to increased obesity and NCDs. 2 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%